Development and evaluation of a newborn care education programme in primiparous mothers in Nepal. (November 2016) - Shrestha, Sharmila; Adachi, Kumiko; Petrini, Marcia A.; Shrestha, Sarita; Rana Khagi, Bina
Abstract: Background: the health and survival of newborns depend on high levels of attention and care from caregivers. The growth and development of some infants are unhealthy because of their mother's or caregiver's lack of knowledge or the use of inappropriate or traditional child-rearing practices that may be harmful. Objective: to develop a newborn care educational programme and evaluate its impact on infant and maternal health in Nepal. Design: a randomised controlled trial. Participants: one hundred and forty-three mothers were randomly assigned to the intervention ( n =69) and control ( n =74) groups. Eligible participants were primiparous mothers who had given birth to a single, full-term, healthy infant, and were without a history of obstetric, medical, or psychological problems. Methods: prior to being discharged from the postnatal unit, the intervention group received our structured newborn care education programme, which consisted of one-on-one educational sessions lasting 10–15 minutes each and one postpartum follow-up telephone support within two weeks after discharge, in addition to the hospital's routine general newborn care education. The control group received only the regular general newborn care education. Outcomes were measured by using Newborn care Knowledge Questionnaires, Karitane Parenting Confidence Scale, State-Trait Anxiety Inventory for Adults and infant health and care status. Findings: the number of mothers attending the health centre due to the sickness of their babies was significantly decreased in the intervention group compared to the control group. Moreover, the intervention group had significant increases in newborn care knowledge and confidence, and decreases in anxiety, compared with the control group. Conclusions: the structured newborn care education programme enhanced the infant and mother health. Moreover, it increased maternal knowledge of newborn care and maternal confidence; and reduced anxiety in primiparous mothers. Thus, this educational programme could be integrated into routine educational programs to promote maternal and infant well-being in Nepalese society. Highlights: Educational motivation and support improve maternal and infant health. Educational support from health professionals promotes maternal and infant health. This educational intervention could be integrated into routine educational programme.